Consumers’ preferences for local and imported culinary herbs in Gauteng province, South Africa - Mphafi, Kananelo; Oyekale, Abayomi S; Ndou, Portia (Research in Agriculture Livestock and Fisheries, 2023)
Demand for culinary herbs in many developing countries is currently growing due to the increased perception of their nutritional and medicinal properties. There is a need to understand consumers’ preferences for these products. This study, therefore, analyzed the determinants of consumers’ preferences for locally produced and imported herbs in Gauteng province. The data were collected with a stratified sampling method from 385 respondents using a structured questionnaire. Multinomial logit regression was then employed for data analysis. The results indicated socio-economic factors and product attributes such as labeling, the attractiveness of packaging, and availability as determinants of preference for both local and imported herbs. Based on these findings, the study recommends that the promotion of herbs must be inclusive of both product attributes and socioeconomic factors. Res. Agric. Livest. Fish. 10(1): 61-71